The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/polb.22223
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of large actuation strain in dielectric elastomers

Abstract: Subject to a voltage, a dielectric elastomer (DE) deforms. Voltage‐induced strains of above 100% have been observed when DEs are prestretched, and for DEs of certain network structures. Understanding mechanisms of large actuation strains is an active area of research. We propose that the voltage‐stretch response of DEs may be modified by prestretch, or by using polymers with “short” chains. This modification results in suppression or elimination of electromechanical instability, leading to large actuation stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
229
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(236 citation statements)
references
References 42 publications
2
229
0
Order By: Relevance
“…The shape of (λ) can be readily showed that  B is a monotonically decreasing function of the stretch λ (Kofod et al, 2003;Koh et al, 2011;Suo, 2012). Depending on where the two curves of (λ) and  B intersect, DE transducers can be classified into three types Suo, 2010;Li et al, 2011), as illustrated in Figs …”
Section: Three Types Of De Transducersmentioning
confidence: 99%
“…The shape of (λ) can be readily showed that  B is a monotonically decreasing function of the stretch λ (Kofod et al, 2003;Koh et al, 2011;Suo, 2012). Depending on where the two curves of (λ) and  B intersect, DE transducers can be classified into three types Suo, 2010;Li et al, 2011), as illustrated in Figs …”
Section: Three Types Of De Transducersmentioning
confidence: 99%
“…To precisely analyze effect of the passive region, its inhomogeneous stress field should be analyzed considering a continuous deformation between the passive and active region as demonstrated by Koh et al 9 and Plante and Dubowsky. 14 In conclusion, we demonstrated that the existing theoretical guidelines for large actuation strains based on VHB films cannot be directly implemented for castable elastomers.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…1 More recently, Rosset et al have shown a 60% linear planar strain on a PDMS based DEA with rise time of less than 10 ms. 8 However, the existing theoretical guidelines for large actuation deformation of DEAs developed based on VHB films cannot be directly implemented to castable elastomers. 9,10 Unlike VHB, which is available as films with predefined thicknesses, PDMS or polyurethane are initially a resin and can be casted to form membranes of any desired thickness. This decouples the thickness of the elastomer from the prestretch ratio allowing to select them independently.…”
Section: Improved Electromechanical Behavior In Castable Dielectric Ementioning
confidence: 99%
“…While large voltage-induced deformation has been demonstrated for an elastomer sheet under equal-biaxial forces, [24][25][26] only small voltage-induced deformation has been observed for an elastomer sheet under a uniaxial force. 27 Many applications, however, require muscle-like actuators in which a voltage induces large and unidirectional displacement.…”
mentioning
confidence: 99%